A multidimensional analysis of environmental awareness: The moderating effect of institutional trust - Dantas, Diogo; Gomes, Sofia (International Journal of Management and Sustainability, 2025)
The research aims to examine global environmental awareness and recognises the need to employ four behavioural dimensions (affective, cognitive, dispositional, and active) into a structured model. We also include trust in institutions to understand its moderating effect on individuals’ behaviour. The study used a broad sample from the ISSP in 29 countries and 44,400 individuals between October 2019 and May 2023. The quantitative model was tested with SmartPLS 4. All the hypotheses were confirmed. The affective dimension of environmental awareness positively affects its cognitive dimension. Both the affective and cognitive dimensions have a positive influence on the dispositional dimension. The dispositional dimension positively influences its active dimension. Trust in institutions positively moderates the relationship between the dispositional and active dimensions. Our research demonstrated that each person simultaneously acts as a change agent based on their perception of personal responsibility and as a consumer, a concept that managers strive to comprehend. Previous research was validated by establishing a causal link between different dimensions of behavior. Managers must focus on integrating the factors that influence pro-environmental behaviour. Governments are essential in changing mentalities and turning dispositional attitudes into effectively active behaviours.